2010
DOI: 10.1257/aer.100.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Trade and Carbon Taxes

Abstract: We study various scenarios for taxing emissions of carbon dioxide (CO 2 ). The question is how carbon tax policies will perform, given international trade, if countries adopt different tax rates. We investigate this question quantitatively using CIM-EARTH, a newly developed open-source computable general equilibrium (CGE) model.Since climate change is a function of global CO 2 emissions, an efficient strategy for controlling emissions would be to impose the same price wherever they occur. Such an approach pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
115
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(118 citation statements)
references
References 2 publications
1
115
0
2
Order By: Relevance
“…To discuss the impacts of the BTAs on China's sectoral carbon emissions, three scenarios are developed under which carbon tariffs will be implemented at different rates, i.e., US dollars 20, 50 and 80 per ton carbon emissions (US$/tce), respectively, according to recent literatures (Peterson and Schleich, 2007;Elliott et al, 2010). In each case, the BTAs measure will be imposed since the year 2020.…”
Section: Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…To discuss the impacts of the BTAs on China's sectoral carbon emissions, three scenarios are developed under which carbon tariffs will be implemented at different rates, i.e., US dollars 20, 50 and 80 per ton carbon emissions (US$/tce), respectively, according to recent literatures (Peterson and Schleich, 2007;Elliott et al, 2010). In each case, the BTAs measure will be imposed since the year 2020.…”
Section: Scenariosmentioning
confidence: 99%
“…On the other hand, some studies have concluded that BTAs would be ineffective either to increase domestic competitiveness or to improve global environment (Weber and 5 Peters, 2009;Dong and Whalley, 2009a,b;Elliott et al, 2010). For example, Lessmann et al (2009) suggested that the leakage avoiding effect of BTAs would be small.…”
Section: Introductionmentioning
confidence: 99%
“…This paper provides the first econometric ex post analysis of the Kyoto Protocol, thereby complementing computable general equilibrium (CGE) analyses such as the one by Elliott et al (2010). For this purpose, it assembles a new panel database on the carbon footprint of nations.…”
Section: Introductionmentioning
confidence: 99%
“…A third group at the University of Chicago built CIM-EARTH, used by Elliott et al (2010a) to simulate different levels of carbon tax in Annex B countries of the Kyoto Protocol. They find that the "increase in emissions by non-Annex B countries relative to the reduction by Annex B countries, the standard measure of carbon leakage, ranges from 15 percent at low tax rates to over 25 percent for the highest tax rate" (p. 468).…”
Section: A Brief Review Of Some Literaturementioning
confidence: 99%
“…In their model, the two sectors might produce two different goods in a closed economy, or they might 1 CGE models and results reviewed below include those of Fischer and Fox (2010) and Böhringer, Carbone, and Rutherford (2011), as well as MIT's "Emissions Prediction and Policy Analysis" (EPPA) model used by Paltsev (2001), Babiker (2005), and Winchester et al (2011). In this paper, we use the "Community Integrated Model of Economic and Resource Trajectories for Humankind" (CIM-EARTH), a relatively new model of Elliott et al (2010aElliott et al ( , 2010b. represent two countries that each produces a unique good.…”
mentioning
confidence: 99%